Code-Switching and Borrowing in Algeria - Ahmed SID, Haoues (Journal of Human Sciences, 2009)
In Algeria, the coexistence of Arabic and French for a certain period of time has led to the emergence of language phenomena which may be found with varying degrees in many bilingual societies. Using an ethnographic approach, a sample of students at Mentouri University, Constantine, was recorded to identify and investigate mixing patterns. The paper first looks at the linguistic research on the structural features of code-switching focusing in particular on the code-switching versus borrowing distinction. Then, it analyses the different mixing patterns according to phonological and/or morphological integration. Finally, results reveal that although code-switching and borrowing are distinct phenomena, they may both be used within the same utterance.